Diamond detectors for dose and instantaneous dose-rate measurements for ultra-high dose-rate scanned helium ion beams - Tessonnier, Thomas; Verona-Rinati, Gianluca; Rank, Luisa; Kranzer, Rafael; Mairani, Andrea; Marinelli, Marco (Medical physics, 2023)
Background The possible emergence of the FLASH effect—the sparing of normal tissue while maintaining tumor control—after irradiations at dose-rates exceeding several tens of Gy per second, has recently spurred a surge of studies attempting to characterize and rationalize the phenomenon. Investigating and reporting the dose and instantaneous dose-rate of ultra-high dose-rate (UHDR) particle radiotherapy beams is crucial for understanding and assessing the FLASH effect, towards pre-clinical application and quality assurance programs. Purpose The purpose of the present work is to investigate a novel diamond-based detector system for dose and instantaneous dose-rate measurements in UHDR particle beams. Methods Two types of diamond detectors, a microDiamond (PTW 60019) and a diamond detector prototype specifically designed for operation in UHDR beams (flashDiamond), and two different readout electronic chains, were investigated for absorbed dose and instantaneous dose-rate measurements. The detectors were irradiated with a helium beam of 145.7 MeV/u under conventional and UHDR delivery. Dose-rate delivery records by the monitoring ionization chamber and diamond detectors were studied for single spot irradiations. Dose linearity at 5 cm depth and in-depth dose response from 2 to 16 cm were investigated for both measurement chains and both detectors in a water tank. Measurements with cylindrical and plane-parallel ionization chambers as well as Monte-Carlo simulations were performed for comparisons. Results Diamond detectors allowed for recording the temporal structure of the beam, in good agreement with the one obtained by the monitoring ionization chamber. A better time resolution of the order of few μs was observed as compared to the approximately 50 μs of the monitoring ionization chamber. Both diamonds detectors show an excellent linearity response in both delivery modalities. Dose values derived by integrating the measured instantaneous dose-rates are in very good agreement with the ones obtained by the standard electrometer readings. Bragg peak curves confirmed the consistency of the charge measurements by the two systems. Conclusions The proposed novel dosimetric system allows for a detailed investigation of the temporal evolution of UHDR beams. As a result, reliable and accurate determinations of dose and instantaneous dose-rate are possible, both required for a comprehensive characterization of UHDR beams and relevant for FLASH effect assessment in clinical treatments.
Gesehen am 15.11.2023